Species diversity and risk factors of gastrointestinal nematodes in smallholder dairy calves in Kenya - Cheptoo, Sylvia; Yalcindag, E.; Gordon, L.G.; Rukwaro, Benson; Kimatu, Joseph S.; Wasonga, Joseph; Karani, Benedict E.; Ndambuki, Gideon; Migeni, Susan; Kagai, Jesse; Kiprotich, Linus E.; Saya, Nelson; et al. (Frontiers Media, 2025)
Gastrointestinal nematodes (GIN) are of major concern in dairy farming, particularly in smallholder systems, because of their impact on the health of the calves and later on their productivity. These infections often occur as co-infections, which can complicate their prevention and treatment. The aim of this study was to conduct fecal egg counts (FEC), genetically identify GIN species, assess species diversity, and identify associated risk factors for GIN infections in dairy calves. Fecal samples were collected from 532 dairy calves across 289 small holder dairy farms. Species identification was achieved through deep amplicon sequencing of the Internal Transcribed Spacer-2 rDNA locus (ITS-2) of first-stage larvae (L1). The mean eggs per gram (EPG) was 62.0 ± 93.0. Most of the calves 64.2% had low-intensity infections (<50 EPG), 28.6% had medium-intensity infections (50–200 EPG), and 7.2% had high-intensity infections (>200 EPG). Next Generation Sequencing analysis identified nine GIN species, with Cooperia punctata (27.8%), Haemonchus placei (26.3%), and Haemonchus contortus (23.6%) being the most prevalent. Co-infections were common, accounting for 69.5% of all infections, with two (40.1%), three (26.9%), and four-species combinations (19.8%) predominating. Male calves showed a significant association with both increased FEC and smaller heart girth, while FEC decreased with age. H. placei and C. punctata were associated with increased FEC, whereas Ostertagia ostertagi (14.5%) and Trichostrongylus colubriformis (8.0%) were associated with decreased heart girth. Calves managed under pasture systems had higher odds of co-infection. This study reveals that GIN infections are highly prevalent in dairy calves, with co-infections being common, and that GIN burden is significantly influenced by calf age, sex, and management system. The Nemabiome tool offers a promising approach to assessing GIN burden and guiding the selection of anthelmintic protocols as part of sustainable farming strategies in tropical regions.